Redesign Logo Duta Minang Wedding Organizer And Planner - Melisa Suardi; Wilma Sriwulan; Syafwandi Syafwandi (Besaung : Jurnal Seni Desain dan Budaya, 2019)
AbstractA company must have a logo as an identity so that people can be known as consumers to consume the products they sell. Redesign the logo at an Ambassador Minang Wedding Organizer and Planner company, which is located at Jl. Rajawali No 09 Padang. done if the old logo does not meet the requirements, including: (1) it is not feasible to be used on the application media; (2) changes in the company's vision and mission; (3) the use of logos that do not function as they should; (4) the ineffectiveness of the logo to be recognized by the public; and (5) to the inconsistency in the form of logos to be used in media that will be a promotional place for companies. Just like the Ambassador of Minang, Wedding Organizer and Planner, who indeed left a logo on several media applications, and favored the name of the company just to be known by the public and applied the name to several print media. So it is necessary to design a logo regarding Ambassador Minang Wedding Organizer and Planner. In the design of the Ambassador of Minang Wedding Oragnizer and Planner logo, the designer uses the AIDA logo method of analysis as a promotional tool that must attract attention, get and encourage interest, generate desire, and produce action on the product. As the identity of the company, the logo requires a design that is simple, easy to remember, flexible and dynamic. The logo as a visual identity to create product productions in the form of the target audience's mind and the creation of a new logo will build the image of the community to the Ambassador of Minang, Wedding Organizer and Planner. The purpose of designing the design of the Ambassador of Minang Wedding Organizer and Planner to achieve the wishes of the Minang Ambassador Wedding Organizer and Planner became a service company with complete and sought-after equipment and equipment in the city of Padang. The redesign of the company's logo can form a new character from the company that is accompanied by changes in the new vision and mission that are used today.Keywords : Design, Logo, Ambassador Minang Wedding Organizer and PlannerAbstrakSebuah perusahaan wajib memiliki logo sebagai identitas agar dapat dikenal oleh masyarakat sebagai konsumen untuk mengkonsumsi produk yang mereka jual. Redesign logo pada sebuah perusahaan Duta Minang Wedding Organizer and Planner, yang beralamat di Jl. Rajawali No 09 Padang. dilakukan jika logo lama tersebut sudah tidak memenuhi syarat, di antaranya: (1) sudah tidak layak untuk dipakai pada media penerapan; (2) adanya perubahan visi dan misi perusahaan; (3) penggunaan logo yang tidak sesuai fungsi sebagai mana mestinya; (4) tidak efektifnya logo untuk dikenali oleh masyarakat; dan (5) hingga tidak konsistennya bentuk logo untuk dipergunakan pada media-media yang akan menjadi  tempat promosi bagi perusahaan. Sama seperti halnya Duta Minang Wedding Organizer and Planner yang memang sudah meninggalkan logo pada beberapa penerapan media, dan lebih mengunggulkan nama perusahaan saja agar dikenal oleh masyarakat dan menerapkan nama tersebut pada beberapa media cetak. Maka perlu dilakukannya desain sebuah logo mengenai Duta Minang Wedding Organizer and Planner. Dalam desain logo Duta Minang Wedding Oragnizer and Planner ini perancang menggunakan metode analisis AIDA guna logo sebagai alat promosi yang harus menarik perhatian, mendapatkan dan mendorong minat, membangkitkan keinginan, dan mengasilkan tindakan terhadap produk. Sebagai identitas dari perusahaan maka logo diperlukan bentuk desain yang simple,  mudah diingat, fleksibel dan dinamis. Logo sebagai visual identity  untuk menciptakan untuk potitioning product  dalam bentuk benak target audiens dan penciptaan logo yang baru akan membangun image masyarakat kepada Duta Minang Wedding Organizer and Planner. Tujuan dari perancangan desain logo Duta Minang Wedding Organizer and Planner agar tercapainya keinginan Duta Minang Wedding Organizer and Planner menjadi perusahaan layanan jasa dengan perlengkapan dan peralatan yang lengkap dan dicari di Kota Padang. Redesign logo perusahaan ini dapat membentuk karakter baru dari perusahaan yang disertai dengan perubahan visi dan misi baru yang digunakan saat ini.Kata kunci : Desain, Logo, Duta Minang Wedding Organizer and Planner